MENGENALKAN MODEL PENGAJARAN EDUTAINMENT (PICTURE AND PICTURE) UNTUK MENGAJARKAN BAHASA INGGRIS PADA ANAK–ANAK USIA DINI - nurjanah nurjanah (Faktor Jurnal Ilmiah Kependidikan, 2015)
Abstract: The purpose of the public service activity was to improve the young children ability in English language learning. We used the model of edutainment (picture and picture) that applied a number of interesting pictures. The audience of this activity is 30 children who live at Choblong village. The result of this activity was the good ability in catching the material of learning fast and proactive.Key words: English learning, the model of edutainment